Analisis Perbandingan Compute Engine dan Cloud Run sebagai lingkungan Pengembangan Aplikasi Web di Google Cloud Platform - Kejora, Cahyo Bintang; Susetyo, Yeremia Alfa (STIKOM Tunas Bangsa Pematangsiantar, 2024)
Cloud computing has become a significant issue in the world of Information and Communication Technology. A leading retail company in Indonesia, PT XYZ, faces challenges in choosing cloud computing services for their application development and operations. The company is faced with a choice between Compute Engine and Cloud Run on Google Cloud Platform. This research aims to analyze the comparison between the two services. By designing a web application which will then be deployed on the two cloud services, a comparative analysis of the applications deployed on the two services will then be made. Based on the test results and analysis carried out in this research, Cloud Run stands out in various aspects. From a cost perspective, the setup and performance of Cloud Run offers significant advantages compared to Compute Engine. Thus, this research concludes that Cloud Run is a more optimal choice for PT XYZ in the context of web application development, providing an efficient and economical solution.